Factors influencing health-related quality of life of patients with spinocerebellar ataxia - Weber, Niklas; Buchholz, Maresa; Rädke, Anika; Faber, Jennifer; Schmitz-Hübsch, Tanja; Jacobi, Heike; Klockgether, Thomas; Hoffmann, Wolfgang; Michalowsky, Bernhard (The cerebellum, 2024)
Little is known about the progression of health-related quality of life (HRQoL) and predicting factors in spinocerebellar ataxia (SCA). Such knowledge is crucial to identify modifiable factors promoting everyday life with SCA and attenuating HRQoL decline.
Gesehen am 11.12.2024